Nazaruddin’s Case: the Jakarta Post Reports on a Bribery Attempt Case - Fachru Ridha (Passage, 2013)
This study aims to describe The Jakarta Post structure in reporting the case, to investigate how the major participants are reported in the texts, and to uncover meanings constructed from the text. The study focuses on headline news reporting Nazaruddin’s bribery attempt case which has been published by The Jakarta Post. The analyses of these reports comply with the frameworks of Critical Discourse Analysis, especially Van Dijk framework, Socio Cognitive Approach(SCA)(2009). First, macro propositions and news schemata are examined, described, and interpreted on the level ofmacrostructure and superstructure. Then, these are followed by an examination of participants based on the representations using microstructure analysis. The study finds that the texts are dominated by participants’ comment and there is not any conclusion. The study also finds that there are two major participants in the texts, namely, Nazaruddin and Mahfud; Nazaruddin is represented negatively, while Mahfud is represented positively. Key Words: The Jakarta Post, discourse, macrostructure, superstructure, microstructure, and meaning.